Integration of unmanned aerial vehicles into the construction process: comparison of traditional methods and modern technologies - MOSKOVCHENKO, Danylo; MISHUK, Katerina (Ways to Improve Construction Efficiency, 2025)
The article examines the use of unmanned aerial vehicles (UAVs) in the construction industry as a modern tool that enhances the efficiency, accuracy, and safety of construction processes. The aim of the study is to determine the practical feasibility of using drones in construction by comparing their capabilities with traditional methods. The research focuses on analyzing specific cases of drone applications, such as aerial photography, 3D modeling, monitoring, and inspection of construction sites, to evaluate their effectiveness, cost efficiency, safety on construction sites, and potential limitations. The study aims to identify ways to optimize construction processes using UAVs, including an analysis of their potential to increase efficiency, reduce construction time, and improve the quality of completed work. Various scenarios for drone applications are analyzed, and optimal usage options are determined in terms of economic efficiency. Special attention is given to assessing the long-term prospects and return on investment in unmanned technologies. The research employs methods of comparative analysis of traditional and unmanned technologies, particularly in aerial photography, 3D modeling, monitoring, and inspection of construction sites. The study focuses on evaluating the efficiency of drones compared to traditional surveying tools and methods. The results demonstrate that UAVs significantly reduce the time required to complete construction tasks, lower costs, and improve the accuracy of collected data. Drones also greatly enhance worker safety by performing tasks in hard-to-reach or hazardous areas. The use of UAVs in construction opens up new possibilities for process optimization, reduces costs, and improves work quality. The research confirms that integrating UAVs into construction projects has a substantial positive impact on the efficiency and safety of construction processes, making them more predictable and manageable.